COVID‐19 stigma in New Zealand: Are we really a 'team' of five million?. (23rd November 2021) - Ergler, Christina; Huish, Robert; Georgeou, Nichole; Simons, Jeremy; Eyles, Olivia; Li, Yi; Deng, Tianran; Tame, Lilian
Abstract: The New Zealand government has used public health ordinances to impose restrictions on immigration, movement and social gatherings for managing the pandemic. Yet, this response led to unintended consequences, in particular the stigmatisation of some communities and professions as being 'diseased'. Such discourse ran contrary to the government's own, and very public assertions, that New Zealand was a 'team of five million' who should 'be kind' to each other. Here, we position stigma as a form of slow violence, which during the pandemic has exploited existing cracks in social cohesion. We then employ an ethics of care approach to suggest some practical responses to healing the rifts created by COVID‐19.